A geografia do voto em eleições municipais no sistema eleitoral de lista aberta: um estudo a partir de Belo Horizonte, Rio de Janeiro e São Paulo - Lucas de Oliveira Gelape (2017)
This masters thesis investigates the spatial distribution of elected city councilmen votes, in the cities of São Paulo, Rio de Janeiro and Belo Horizonte, in the 2008 and 2012 elections. Its main goal is to identify these politicians voting patterns, examining the principal meansnamed by the literature to do so. Therefore, this study offers contributions to three fields in political science: (1) electoral geography; (2) open list electoral systems; (3) local politics. At first, it is presented a literature review of the fundamental researches which concern this thesis, laying the theoretical foundations of this study. Subsequently, the research design is introduced, highlighting that the strategy adopted to identify the voting patterns is to classify the city councilmen conforming to Barry Amess taxonomy proposal, which consists in classifying the candidates in four different types, according to two dimensions (horizontal andvertical) of its votes spatial distribution: (1) concentrated-dominant; (2) concentrated-shared; (3) scattered-shared; and (4) scattered-dominant. The indexes used in the literature to classify the candidates in the previous types are also examined. The final chapter presents theempirical findings of this research, underlining the choice of which seems to be the most appropriate indexes and classification criteria to measure each dimension in the cases studied. The findings point out to stability in the number of councilmen of each type in the same citybetween the two elections; and also a predominance of the scattered-shared type in all of the cities and elections studied.